Dosis de microorganismos eficaces (EM-1) con abonamiento uniforme de vacaza y su efecto sobre las características agronómicas del pasto Panicum máximum CV. mombaza en Zungarococha, Perú – 2018 - Ormeño Tananta, Angel Edrulfo (2019)
The use of probiotics as effective microorganisms in pasture production is one of the agro-environmental alternatives for the production of sustainable forage since it improves soils and protects plants, increasing their growth and development, the Faculty of Agronomy of UNAP carried out the present research work entitled "DOSES OF EFFECTIVE MICROORGANISMS (EM-1) WITH UNIFORM FERTILIZATION OF VACAZA AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS OF THE PASTURE Panicum Maximum CV. MOMBAZA IN ZUNGAROCOCHA, PERU - 2018 ", with five treatments and four repetitions with a completely randomized block design with the following treatments, A complete randomized block design was used with 5 treatments and 4 repetitions, with the following treatments T0 (0% EM Solution), T1 (2.5% EM Solution), T2 (5% EM Solution), T3 (7.5% EM solution) and T4 (10% EM solution), reaching the following conclusions: plant height increased in relation to the application of the effective microorganisms EM-1, such that treatment T4 (10% EM solution) obtained the best results with 133.73 cm, green matter of 3.53 kg/m2, dry matter of 0.71 kg/m2, coverage percentage of 96.60%, and a yield of 35,300 kg/ha. From this, it can be concluded that a higher dose of efficient macroorganisms (EM-1) increases the results of the dependent variables.